Cures vs. profits successes in translational research - Lyons-Weiler, James (Singapore : World Scientific Publishing Co. Pte Ltd, 2016)
'Did you ever wonder whether doctors want cures, or just treatments? Did you know ... Grapefruit can interact with over 100 drugs, but it may be useful for reducing blood pressure and for weight loss? ADHD over diagnosis is now recognized widely as a fact, and there are existing and new ways to avoid a misdiagnosis? Studies have been conducted demonstrating the utility of Omega 3 fatty acids, meditation, yoga, and melatonin for some important symptoms of ADHD, including executive functions? Vaccines have saved millions of lives in the last decade? But are they safe? Breast cancer rates are declining in the US, but have been steadily increasing in Japan? Doctors are getting better at predicting which chemotherapy will, and will not work, on certain cancers? There are vaccines against cancer? This book reviews recent key, hard-won successes and findings from recent biomedical research. Written by one of the most ardent defenders of the public trust in science, it provides an accessible, detailed look at successes in translational biomedical and clinical research. The author provides an optimistic, forward-looking view for the possibility of change for the public good, cutting through the controversy and gets to very core of each topic. The public can be optimistic about the future of medicine, but only if they learn the facts of these advances, and learn what their doctors should be expected to know. Highly referenced, and filled with interviews from experts and people directly involved in the research behind the new facts in each chapter, this book is a rich source of information on advances in biomedicine that you will want to share with your family & friends.'--Provided by publisher.
Title from PDF file title page (viewed May 25, 2016).
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Medicine -- Research -- History; Medicine -- Research -- Moral and ethical aspects; Medical innovations -- History; Electronic books